The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1021/ef500034j
|View full text |Cite
|
Sign up to set email alerts
|

Wettability Evaluation of a CO2/Water/Bentheimer Sandstone System: Contact Angle, Dissolution, and Bubble Size

Abstract: The success of CO 2 storage in deep saline aquifers and depleted oil and gas reservoirs is largely controlled by interfacial phenomena among fluid phases and rock pore spaces. Particularly, the wettability of the rock matrix has a strong effect on capillary pressure, relative permeability, and the distribution of phases within the pore space and thus on the entire displacement mechanism and storage capacity. Precise understanding of wettability behavior is therefore fundamental when injecting CO 2 into geologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(54 citation statements)
references
References 60 publications
3
49
0
Order By: Relevance
“…As the pressurized CO 2 is pumped underground, it warms to in situ temperature of the storage reservoir; under the pressure and temperature conditions of most reservoirs targeted for CO 2 sequestration, the injected CO 2 will exist in a supercritical state (denoted scCO 2 in the present study) [Intergovernmental Panel on Climate Change, 2005;Benson and Cole, 2008]. Sandstones and other sedimentary formations provide favorable storage conditions [Bachu, 2003;Gunter et al, 2004]; and although wettability measurements of scCO 2 -brine-geologic media systems are thus far inconclusive [Wan et al, 2014], for sandstone formations, aqueous brine has been observed to be the dominant wetting phase while scCO 2 is the nonwetting phase Krevor et al, 2012;Pini and Benson, 2013;Herring et al, 2014;Kaveh et al, 2014]; these observations are supported by measurements of water-wet (or weakly water-wet) contact angles on surfaces representative of sandstones [Chaudhary et al, 2015]. The nomenclature used in the following reflects this assumption of water-wet porous media.…”
Section: Introductionmentioning
confidence: 89%
“…As the pressurized CO 2 is pumped underground, it warms to in situ temperature of the storage reservoir; under the pressure and temperature conditions of most reservoirs targeted for CO 2 sequestration, the injected CO 2 will exist in a supercritical state (denoted scCO 2 in the present study) [Intergovernmental Panel on Climate Change, 2005;Benson and Cole, 2008]. Sandstones and other sedimentary formations provide favorable storage conditions [Bachu, 2003;Gunter et al, 2004]; and although wettability measurements of scCO 2 -brine-geologic media systems are thus far inconclusive [Wan et al, 2014], for sandstone formations, aqueous brine has been observed to be the dominant wetting phase while scCO 2 is the nonwetting phase Krevor et al, 2012;Pini and Benson, 2013;Herring et al, 2014;Kaveh et al, 2014]; these observations are supported by measurements of water-wet (or weakly water-wet) contact angles on surfaces representative of sandstones [Chaudhary et al, 2015]. The nomenclature used in the following reflects this assumption of water-wet porous media.…”
Section: Introductionmentioning
confidence: 89%
“…[] and Kaveh et al . [], contact angle measurements depend on equilibration time between the fluids and the solid and on bubble size. They found that contact angle increases with progressing equilibration time but decreases with bubble radius if placed underneath the solid surface.…”
Section: Co2‐wettability Of Caprock and Storage Rock Mineralsmentioning
confidence: 99%
“…Kaveh et al . [] measured captive drop contact angles for the Bentheimer sandstone‐CO 2 ‐water system. The sandstone consisted of 96% quartz, ∼2% feldspars, and ∼2% kaolinite, and the kaolinite was homogeneously distributed throughout the rock matrix.…”
Section: Co2‐wettability Of Caprock and Storage Rock Mineralsmentioning
confidence: 99%
“…Furthermore, wettability alteration by CO 2 dissolution in brine has already been investigated for the systems of CO 2 -water-coal 9-11 , CO 2 -brine-Mica 12, 13 , CO 2 -brine-Quartz 12, 14 , CO 2reservoir brine-reservoir rock [15][16][17][18] and CO 2 -water-glass 19,20 ; however, very limited study focus on the wettability alteration of oil-brine-rock system with dissolution of CO 2 21 . Grape et al 22 performed imbibition tests involving CO 2 -enriched water (carbonated water).…”
Section: Introductionmentioning
confidence: 99%